2019
DOI: 10.1186/s12960-019-0428-7
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with physician assistant/associate care: an international scoping review

Abstract: BackgroundAs the role of the physician assistant/associate grows globally, one question is: what is the level of patient satisfaction with PAs? Driven by legislative enactments to improve access to care, the PA has emerged as a ready and able medical professional to address workforce shortages. The aim of this study was to review the literature on patient satisfaction of PAs.ObjectivesThe basis for this review was to clarify working definitions, synthesize the evidence, and establish conceptual boundaries arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 33 publications
3
52
0
1
Order By: Relevance
“…In our study, we found that while there is limited understanding of the NP role amongst the Australian public, this had no relationship to their willingness to receive treatment and autonomous episodes of care from an NP. Indeed, a recent international scoping review of patient satisfaction with independent care provided by adjunct health care providers, such as the physician assistants, found that people are generally satisfied with care received, regardless of medical provider [ 23 ]. Health care consumer support, willingness and acceptance for autonomous and complementary models of health care are fundamental to informing policy change [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, we found that while there is limited understanding of the NP role amongst the Australian public, this had no relationship to their willingness to receive treatment and autonomous episodes of care from an NP. Indeed, a recent international scoping review of patient satisfaction with independent care provided by adjunct health care providers, such as the physician assistants, found that people are generally satisfied with care received, regardless of medical provider [ 23 ]. Health care consumer support, willingness and acceptance for autonomous and complementary models of health care are fundamental to informing policy change [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The scope of the Australian NP practice includes: managing patient episodes of care, initiation and interpretation of diagnostic and pathology investigations, endorsement to prescribe medications, patient education and health promotion, admission and discharge rights and referrals for specific patient groups [ 10 , 11 , 18 – 21 ]. As increasingly more NPs are getting established in the Australian public sector workforce [ 17 , 22 ] and to a lesser extent in the private, community and primary care settings [ 12 ], the question as to what patients want continues to emerge [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Satisfaction came along quickly. Patients were willing to see any reliable health provider as long as their needs were met, and quality was not compromised [10].…”
Section: Discussionmentioning
confidence: 99%
“…Patient acceptance of PAs is positive across four continents and their willingness to see a PA is growing. [1] However, the acceptance of PAs from the perspective of medical students has not been explored. According to Stone (2018) the delivery of quality, cost-effective medical care is increasingly relying upon team-based care.…”
Section: Introductionmentioning
confidence: 99%